Effect of Normal or Blended Funny Discussion on Development of Meta-reading Skills and The Ability to Choose Teaching Method - Jahjouh, Yahya Mohmmad Abu (Jurnal Pendidikan Progresif, 2020)
Effect of Normal or Blended Funny Discussion on Development of Meta-reading Skills and The Ability to Choose Teaching Method. Objectives: The present research aimed to investigate the effect of using the funny discussion strategy (conventional as compared to the blended discussion strategy) on the development of meta-reading skills and the ability to choose the appropriate teaching method among science teaching students in the faculty of education at Al-Aqsa University in Gaza. Method: The researcher followed the experimental method and designed a questionnaire of meta-reading skills and a test of choosing the appropriate teaching method. Findings: There were no statistically significant differences between the mean scores of the meta-reading skills of the students of the two experimental groups. However, the students of the two experimental groups outperformed the students of the control group in the ability to choose the teaching method. Conclusions: funny discussion strategy can be employed independently or in combination with modern technology, and the strategy of funny discussion is suitable for teaching strategies for the students of the faculty of education. Keywords: strategy of normal funny discussion, the strategy of blended funny discussion, meta-reading skills, choice of the teaching method. DOI: http://dx.doi.org/10.23960/jpp.v10.i3.202007